The Influence of the Wafa Method on the Qur'an Reading Ability of Seventh Grade Students of SMP Cendekia Madani Metro - Irsyad Hanafi Irsyad; Hernisawati; Choirudin (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to determine the influence of the Wafa method on the Qur'an reading ability of seventh-grade students of SMP Cendekia Madani Metro. The research is motivated by the low level of students' Qur'an reading ability and the need for effective, systematic, and engaging learning methods. The Wafa method is an innovation in Qur'anic learning that integrates the right-brain approach with the 5P learning system (Opening, Experience, Teaching, Assessment, Closing) and the Hijaz melodic tone. This study employed a quantitative approach with a causal-associative survey design. The study population consisted of all seventh-grade students, totaling 30 individuals, all of whom were selected as samples using a saturated sampling technique. Data collection techniques included questionnaires, a Qur'an reading test, and documentation. Data analysis was performed using the Pearson Product-Moment correlation test with SPSS version 22. The results showed a correlation coefficient (r_xy) of 0.399 with a calculated t-value (2.722) greater than the t-table value (2.048) at a 5% significance level, thus the alternative hypothesis (Ha) was accepted. The relationship between the two variables fell into the low category, with the Wafa method contributing 15.9% (coefficient of determination) to Qur'an reading ability, while the remaining 84.1% was influenced by other factors such as learning motivation, teacher guidance, family environment, and internal student factors. Accordingly, the Wafa method has a positive yet still relatively low influence on students' Qur'an reading ability, indicating a need for optimal implementation of this method.